The identity of Schizoglossum theileri (Apocynaceae, Asclepiadoideae) - Bester, Stoffel Petrus; Glen, Melissa, F.; Nicholas, Ashley (Phytotaxa, 2016)
Schizoglossum theileri (Apocynaceae, Asclepiadoideae) is found to be conspecific with Asclepias meliodora and is here formally reduced to synonymy under the latter.